T. B. BOBER: NOMINATION OF FOOTWEAR IN MID-UPPER-DNIEPER DIALECTS - BOBER, T. B. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. This article on the material collected in modern Mid-Upper-Dnieper dialects, the principles of nomination of footwear are investigated. The motivational features that influenced the nomination are determined, basic motivational models are established and the word-forming means of the units of the named lexical-semantic group are analyzed. Purpose. The representation of lexical unit repertoire of some household vocabulary gives an opportunity to investigate the repertoire and principles of nomination of footwear in modern Mid-Upper Dnieper dialects. Methods. To achieve the goal set, the following methods of scientific investigation are applied: expedition (to fix dialectal material), description (to register and systematize material), comparative analysis (to compare the names of footwear at different time slices), component analysis (to split the meaning of a word into its elementary meanings). Results. Linguistic and ethnographic sources on the research topic are analyzed in the article. The repertoire of lexical units is partially kept in the speech of older dialect speakers. The complex of nomination footwear is supplemented by new tokens. The nomination is represented by specific Slavic names and borrowings. Originality. A new factual material showing principles of nomination of names of footwear from the Mid-Upper Dnieper dialects is recorded for the first time in the modern Mid-Upper Dnieper dialects by expeditions. The obtained data complete the information on the vocabulary of the Mid-Upper Dnieper dialects. Conclusion. The lexical-semantic group of footwear has a branched structure. The more productive differential features that influenced the nomination include the “material”, “cut”, “color”, “decoration”, “wearing time” of reality. The task of future studies is to replenish the repertoire of names of footwea from the Mid-Upper Dnieper dialects, to deepen the analysis of the principles of nomination, to find out the main ways and means of naming.